ผลของโปรแกรมการเสริมสร้างสมรรถนะแห่งตนต่อพฤติกรรมเลิกสูบบุหรื่ของผู้ป่วยโรคหลอดเลีอดหัวใจตีบหลังได้รับการขยายหลอดเลือดโคโรนารี - พัชรินทร์ อินทร์ปรุง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this quasi-experimental research was to study the effect of self-efficacy promoting program on smoking cessation behavior in patients after undergoing percutaneous coronary intervention. Samples were 40 adults patients with coronary artery disease who reseived percutaneous coronary intervention at heart clinic, out patient department, Phramongkutklao Hospital. The samples were assigned in to the experimental and the control group, matched in terms of gender, age, nicotine level, attempt to try of quit smoke and the methods of quit smoke. The experimental group received the perceived self-efficacy promoting program smoking cessation, and the control group received a conventional nursing care. Self-efficacy Theory (Bandura, 1997) were used as a conceptual framework. The instruments were Perceived Self-efficacy Questionnaires and Smoking Behaviors Questionnaires and tested for the content validity by 5 experts. The reliabilities of were .89 and .87, respectively. Data were analyzed by using percentage, mean, standard deviation, and t-test. Major findings were as following: 1. The mean score of smoking cessation behavior after participating in the changing behavior program was significantly higher than before participating in the program at the level of .05 2. The mean score of smoking cessation behavior after participating in the program of the experimental group was significantly higher than that of the control group at the level of .05